Perlindungan Hukum Bagi Konsumen Jual Beli Pakaian Bekas Di Kota Ambon - Latuconsina, Moh Fadly; Berlianty, Teng; Balik, Agustina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: There are lots of used clothes being traded in markets and through online shops in the city of Ambon. These consumer rights can be violated by the seller if the consumer unknowingly sees the sale of imported used clothing which is rife in the domestic market to buy clothes that contain lots of bacteria.Purposes of the Research: This study aims to examine the forms of legal protection for consumers for buying and selling used clothing and the responsibility of business actors for consumers of used clothing who are harmed in terms of health.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The form of legal protection for consumers for buying and selling used clothes is by issuing Law no. 8 of 1999 concerning consumer protection is meant to be a strong legal basis for the government and consumer protection agencies as an effort to empower consumers through fostering and protecting all buying and selling activities that are detrimental to consumers, in this case used clothing illegally smuggled into various regions without regard to the adverse effects of the used clothes. The responsibility of business actors to consumers of used clothes who are harmed in terms of health. The responsibility of business actors can be requested when business actors violate consumer rights and commit acts that are prohibited according to Article 8 of Law Number 8 of 1999 concerning Consumer Protection, namely business actors are prohibited from trading goods that damaged, defective or used, and polluted without providing complete and correct information on the goods in question.